2007
DOI: 10.1118/1.2760806
|View full text |Cite
|
Sign up to set email alerts
|

SU-FF-T-147: Determination of TG43 Parameters for Cs-131 Model CS-1R2 Seed Using Radiochromic EBT Film Dosimetry

Abstract: Purpose: To measure the 2D dose distributions for Cs‐131 seed model CS‐1R2 for distances from 0.06cm to 4cm using radiochromic EBT film dosimetry. TG43 dosimetric parameters were generated. Method and Materials: Each radiochromic film (GAFCHROMIC® EBT lot ♯35076) was in contact with a model CS‐1R2 seed (IsoRay Medical) at the center of a solid water phantom, 30×30×20cm. A multiple film technique was employed. More than 50 films were separately exposed to 10 seeds, with the product of air kerma strength and exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Chiu-Tsao et al [56] employed EBT film model to determine the TG-43 (AAPM protocol for brachytherapy dose calculations) parameters for the Cs-131 and Cs-132 seed sources. Le et al [57] used EBT film to assess dose heterogeneity in intra-operative HDR brachytherapy, and Evans et al [58] have demonstrated the use of the radiochromic films in a brachytherapy auto-radiograph QA Figure 6 Justification of the uncertainty estimation analysis: relative percent error in dose delivered (above) and relative one sigma uncertainty (below) for EBT GAFCHROMICä film model (From [22]).…”
Section: Radiochromic Film Applicationsmentioning
confidence: 99%
“…Chiu-Tsao et al [56] employed EBT film model to determine the TG-43 (AAPM protocol for brachytherapy dose calculations) parameters for the Cs-131 and Cs-132 seed sources. Le et al [57] used EBT film to assess dose heterogeneity in intra-operative HDR brachytherapy, and Evans et al [58] have demonstrated the use of the radiochromic films in a brachytherapy auto-radiograph QA Figure 6 Justification of the uncertainty estimation analysis: relative percent error in dose delivered (above) and relative one sigma uncertainty (below) for EBT GAFCHROMICä film model (From [22]).…”
Section: Radiochromic Film Applicationsmentioning
confidence: 99%
“…17 The high spatial resolution, energy independence of response, 18,19 and near tissue-equivalence of EBT film make it suitable for dose distribution measurements in radiation fields with high dose gradients. Apart from the IMRT QA measurements, EBT film model has found use in a number of additional dosimetry applications: brachytherapy, [20][21][22][23] total skin electron therapy ͑TSET͒, 24,25 electron therapy, 26,27 skin dose measurements, 28,29 total body irradiation ͑TBI͒, 30 lung 31,32 and breast 33 phantom measurements, stereotactic radiotherapy, [34][35][36] dosimetry characterization of proton therapy beams, 37 as well as dose verification during cell irradiation in radiobiological experiments. 38 The dynamic range of the EBT model GAFCHROMIC™ film in the red channel of its absorption spectrum is very well suited for dose measurements of up to approximately 8 Gy.…”
Section: Introductionmentioning
confidence: 99%